1995
DOI: 10.1161/01.cir.91.6.1782
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Right Ventricular Diastolic Performance After Complete Repair of Tetralogy of Fallot

Abstract: Isolated right ventricular restriction is characterized by antegrade diastolic pulmonary arterial flow on Doppler echocardiography and is responsible for the slower postoperative course and clinical evidence of low cardiac output state in some patients after complete repair of tetralogy of Fallot.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
172
3
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 260 publications
(181 citation statements)
references
References 14 publications
4
172
3
2
Order By: Relevance
“…Studies in the literature have shown that electrocardiographic, radiological, and clinical alterations may be related to the prognosis of the patient undergoing total repair of tetralogy of Fallot [1][2][3][4][5][6][7][8][9] . Biventricular systolic function is preserved in most patients [2][3][4] .…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Studies in the literature have shown that electrocardiographic, radiological, and clinical alterations may be related to the prognosis of the patient undergoing total repair of tetralogy of Fallot [1][2][3][4][5][6][7][8][9] . Biventricular systolic function is preserved in most patients [2][3][4] .…”
mentioning
confidence: 99%
“…Biventricular systolic function is preserved in most patients [2][3][4] . However, right ventricular diastolic function has been recently observed to show signs of impairment with a diverse behavior in different phases of the postoperative follow-up [2][3][4] .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Three or more loops were stored for subsequent offline analysis. The presence of restrictive right ventricle physiology was defined as antegrade flow across the pulmonary artery coincident with atrial systole in all respiratory cycles [parasternal short axis right ventricle outflow tract view] (Cullen et al 1995).…”
Section: Perioperative Tissue Doppler Echocardiographymentioning
confidence: 99%